Vaccine Type-, Age- and Past Infection-Dependence of the Humoral Response to SARS-CoV-2 Spike S Protein - Romero-Pinedo, Salvador; Quesada, Marina; Horndler, Lydia; Álvarez-Fernández, Stela; Olmo, Asunción; Abia, David; Alarcón, Balbino; Delgado, Pilar (Frontiers in Immunology, 2022)
The emergence of COVID-19 has led to a worldwide challenge for the rapid development of vaccines. Several types of safe and effective vaccines have been available in a time frame never seen before. Now that several hundred million people have been vaccinated there is an opportunity to compare vaccines in terms of protection and immune response. Here, we have applied a highly sensitive multiplexed flow cytometry method to measure simultaneously IgM, IgG1 and IgA anti-spike protein antibodies generated in response to three vaccines: ChAdOx1 (Oxford-AstraZeneca), mRNA-1273 (Moderna), and BNT162b2 (Pfizer-BioNTech). We have found that mRNA vaccines (mRNA-1273 and BNT162b2) induce a stronger humoral response, both after the first and the second dose, than the adenovirus-based ChAdOx1 vaccine. We also found that, in the elderly, antibody titers negatively correlate with the age of the donor but, also, that antibody titers remain stable for at least 6 months after complete vaccination. Finally, we found that one dose of BNT162b2 is sufficient to induce the highest antibody titers in seropositive pre-vaccination donors. We hope these data will help to guide future decisions on vaccination strategies.